2017
DOI: 10.1002/dc.23818
|View full text |Cite
|
Sign up to set email alerts
|

Different expression about induced sputum cell sorting in the two main types of chronic obstructive pulmonary disease

Abstract: These findings suggest that the morphological phenotypes of COPD show several clinical characteristics and different sputum cell sorting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Interestingly, in our study, we found that while changes in neutrophil counts were most closely associated with the cough score, a weekly increase in sputum eosinophils was associated with an increase in dyspnoea score, paralleled by an increase in rescue medications use. These findings expand upon previous observations showing that COPD patients with high sputum eosinophils are more likely to present with exertional dyspnoea, while patients with a neutrophilic phenotype more likely had chronic bronchitis . The mechanisms linking modifications of eosinophilic inflammation with the variability of dyspnoea in COPD are unexplored.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, in our study, we found that while changes in neutrophil counts were most closely associated with the cough score, a weekly increase in sputum eosinophils was associated with an increase in dyspnoea score, paralleled by an increase in rescue medications use. These findings expand upon previous observations showing that COPD patients with high sputum eosinophils are more likely to present with exertional dyspnoea, while patients with a neutrophilic phenotype more likely had chronic bronchitis . The mechanisms linking modifications of eosinophilic inflammation with the variability of dyspnoea in COPD are unexplored.…”
Section: Discussionsupporting
confidence: 82%
“…These findings expand upon previous observations showing that COPD patients with high sputum eosinophils are more likely to present with exertional dyspnoea, while patients with a neutrophilic phenotype more likely had chronic bronchitis. 25 The mechanisms linking modifications of eosinophilic inflammation with the variability of dyspnoea in COPD are unexplored. In asthma, the recruitment and activation of eosinophils led to the release of pro-inflammatory mediators with bronchoconstriction activity.…”
Section: Discussionmentioning
confidence: 99%